2018
DOI: 10.21873/invivo.11155
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Among Breast Cancer Survivors in South Korea: A Nationwide Population-Based Study

Abstract: Abstract. Background Worldwide, breast cancer is the most commonly diagnosed malignancy among women (1). Especially in traditionally low-risk areas, where changes in lifestyle have been significant, breast cancer incidence rates have nearly doubled in recent decades (2). In South Korea, the number of patients diagnosed with breast cancer has rapidly increased, reaching 12,206 in 2012, which was 3-fold higher than 10 years earlier (3). As the number of breast cancer survivors has increased, managing quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The few previous studies in this area have reported high rates of influenza among cancer survivors, consistent with our findings, but have lacked a cancer-free comparison group. [18][19][20][21] Hermann et al investigated outcomes among patients with a history of cancer presenting with influenza, and found no difference in mortality according to haematological or non-haematological cancer type, or activity of the cancer. 18 Our results showed considerably higher risks of hospitalisation or death among haematological cancer survivors, which could be consistent with the findings in Hermann et al if haematological cancer survivors are at increased risk of infection, but not mortality once infected, compared to non-haematological cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few previous studies in this area have reported high rates of influenza among cancer survivors, consistent with our findings, but have lacked a cancer-free comparison group. [18][19][20][21] Hermann et al investigated outcomes among patients with a history of cancer presenting with influenza, and found no difference in mortality according to haematological or non-haematological cancer type, or activity of the cancer. 18 Our results showed considerably higher risks of hospitalisation or death among haematological cancer survivors, which could be consistent with the findings in Hermann et al if haematological cancer survivors are at increased risk of infection, but not mortality once infected, compared to non-haematological cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated vulnerability to influenza infection of any severity; two studies using administrative claims data in South Korea found a high rate of claims for influenza among both breast cancer survivors and survivors of childhood cancers. 19,20 Similarly, Australian survey data found that a large proportion (38%) of hematopoietic stem cell transplant survivors had had influenza-like illnesses in the time (median 5 years) since their transplant suggesting potentially high vulnerability to infection, but there was no control group or information on severity of infection. 21 Direct evidence on how COVID-19 affects cancer patients and survivors is immature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that BC patients treated with chemotherapy stay immuno-compromised for more than a year after treatment ( Carreira et al, 2020 ). A higher prevalence rate of viral infection was reported among BC survivors compared to cancer-free people ( Heo et al, 2017 ).…”
Section: Incidence Of Infection and Severity Of Sars-cov-2 In Bc Patients Is Augmentedmentioning
confidence: 99%
“…Radiation therapy can also lead to cardiovascular complications including coronary artery disease, cardiomyopathy, and myocardial fibrosis [31,32]. Cancer survivors are at increased risk for morbidity and mortality from infections and infection-related complications [33,34]. Indeed, influenza-induced exacerbation of pre-existing cardiovascular diseases is more common among high-risk populations, including cancer survivors [35].…”
mentioning
confidence: 99%